PENGARUH KEPEMILIKAN KELUARGA, KEPEMILIKAN MANAJERIAL, DEWAN KOMISARIS, KOMITE AUDIT DAN AUDITOR EKSTERNAL TERHADAP LUASNYA PENGUNGKAPAN DI LAPORAN TAHUNAN (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Tahun 2012-2013) - Ananda, Ranti Rizki; -, Zulbahridar; -, Hariadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study was aimed to obtain empirical evidence about the influence of ownership structure and board characteristics on voluntary disclosure in the annual reports of existing companies in Indonesia Stock Exchange (ISX) in 2012 and 2013. Ownership structure is characterized by family ownership and managerial ownership while board characteristic is characterized by board of commissioners, audit commitee and accounting firm. The population of this study was the manufactur companies listed in Indonesia Stock Exchange in 2012 and 2013. The checked sample was 105 companies that had been observed for two year, which the total of it was 210 sample. The data analysis was conducted, with the classical assumption and hypothesis testing, by using multiple regression. The results of this study indicated that the factors of family ownership, and accounting firm significantly influenced the voluntary disclosure. Meanwhile, managerial ownership, independent directors and audit comitee had no a significant impact on voluntary disclosure.Keywords: Disclosure, ownership, board of commissioners, and audit.